ANALISIS KEMAMPUAN REPRESENTASI MATEMATIS SISWA PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL (SPLDV) DI KELAS VIII SMP - Firdaus, Andi Mulawakkan (Universitas Pancasakti, 2022)
This research aims to analyze the mathematical representation abilities of students who have high mathematical abilities, moderate mathematical abilities, and low mathematical abilities in solving mathematics problems in class VIII students at SMP Negeri 1 Kuncio Pao. The type of research used is qualitative research. The instruments used were mathematical representation ability tests and interview guidelines. The indicators of mathematical representation ability used in this research are visual indicators, indicators of equations or mathematical expressions and indicators of words or written text. The subjects taken were 3 students, namely 1 subject who had high mathematical abilities, 1 subject who had moderate mathematical abilities, and 1 subject who had low mathematical abilities. The results of the research show that (1) Subjects with high mathematical abilities are able to fulfill all indicators of mathematical representation, namely visual indicators, indicators of equations or mathematical expressions and indicators of words or written text. (2) Subjects with moderate mathematical abilities are only able to fulfill 2 indicators of mathematical representation, namely indicators of equations or mathematical expressions and indicators of words or written text, and are unable to fulfill visual indicators. (3) Subjects with low mathematical abilities are unable to fulfill all indicators of mathematical representation, namely visual indicators, indicators of equations or mathematical expressions and indicators of words or written text.